Reliability of Alcohol Recall After 15 Years and 23 Years of Follow-Up in the Johns Hopkins Precursors Study - Chu, Audrey Y. (Rutgers University, 2010)
OBJECTIVE: Recall of past alcohol intake is used in many studies of chronic disease, but few studies have been able to examine its long-term reliability. METHOD: We sought to assess the reliability of re called alcohol intake assessed at an average age of 70 years in 2001, after 15 and 23 years of follow-up, in a prospective study of medical students in classes 1948 to 1964. RESULTS: Average reported alcohol intake 15 years and 23 years prior were 6.3 and 7.4 drinks per week, respectively. Recall of alcohol intake overestimated the concurrently reported intake after 15 years by a mean of 0.47 (95% CI [0.10, 0.85]) drinks per week and underestimated intake after 23 years by a mean of 0.79 (95% CI [−1.27, −0.30]) drinks per week, mostly driven by differences between concurrently reported and recalled distilled spirits consumption. Characteristics associated with underestimation of alcohol recall were age of 71 years or older in 2001, self-report of memory difficulties, and self-report of difficulties in physical functioning. In multivariate regression analyses combining 15- and 23-year recall, subjects who reported consumption of more than 14 alcoholic drinks per week in 2001 marginally overestimated recall by slightly more than 1 drink per week (M = 1.18 drinks/week, 95% CI [−0.03, 2.40]). CONCLUSIONS: Although significant differences were detected, recalled alcohol intake after 15 and 23 years of follow-up is remarkably reliable.